PEMANFAATAN MEDIA RANGKA AVES DALAM PEMBELAJARAN BIOLOGI UNTUK SISWA KELAS XI IPA MA ALI MAKSUM PADA SUBMATERI POKOK RANGKA - Susilawati, Lela; Pramesti, Dias Idha; Fatmawati, Fatmawati; Hasanah, Uswatun (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
This research aimed to investigate the improvement of learning outcomes and student interest at MA Ali Maksum students on skeletal system materials after the media Aves skeletal system was implemented in the class. This research was carried out by usingÂ  class action executed in two cycles. Every cycle consisted of planning phase, action, observation and reflection. The learning outcomes and students interest were obtained from test (pretest and postest) and questionnaires respectively. The results of this research showed that from cycle I and II, the improved learning outcomes was observed with percentage > 80%. Meanwhile, all student showed the high interest to study skeletal system materials due to of using instructional media of Aves skeletal system during learning process in the class. Finally, it can be concluded that using of Aves skeletal system as instructional media in the class was a quite effective.keywords: instructional media, skeletal system, learning biology